Is lung function associated with bone mineral density? Results from the Hertfordshire Cohort Study - Dennison, E; Dhanwal, D; Shaheen, S; Azagra, R; Reading, I; Jameson, K; Sayer, A; Cooper, C (2013)
Given limited information available regarding associations between lung function and bone mineral density among healthy subjects, we undertook these analyses in the Hertfordshire Cohort Study. Forced expiratory volume in 1 s (FEV1), forced vital capacity (FVC) and FEV1/FVC were not associated with bone mineral density at any site; associations with bone mineral content were removed by adjustment for body size. Purpose: There is limited information available regarding the association between lung function and bone mineral density among healthy elderly subjects. We addressed this issue in the Hertfordshire Cohort Study. Methods: From the above cohort, 985 subjects (496 men and 489 women) aged 60-72 years were recruited. All subjects underwent bone density measurements using dual energy X-ray absorptiometry and lung function tests using standardised spirometry. Chronic obstructive pulmonary disease (COPD) was defined as a FEV1/FVC ratio